IDENTIFICATION OF CHARACTERISTICS OF DYNAMIC STANDS - Кабанячий, В. В. (Proceedings of National Aviation University (archive), 2021)
The mathematical formulation, solution of the identification problem and the characteristics of the dynamic stands of aviation simulators are given.